The genus Athyrium (Woodsiaceae) in Arunachal Pradesh state, India - Chanda, Chhandam; Mitra, Prashanta Kumar; Fraser-Jenkins, Christopher Roy; Rawat, Vineet Kumar (Phytotaxa, 2024)
This paper deals with the diversity and distribution of Athyrium in Arunachal Pradesh, N.E. India. 28 species are reported here from the state. The first authentic report of Athyrium flabellulatum from Arunachal Pradesh is also made here. Taxonomic details of the species are given. The distribution pattern of species by districts is also studied using exploratory data analysis.